Harmonic development and biodiesel - Szántó, Zsuzsanna; Sinóros-Szabó, Botond (Acta Agraria Debreceniensis, 2010)
An increased expansion of renewable resources and biodiesel is observed and prognosed, since fossile energy resources are about to run out. Hungary achieved outstanding sunflower years in the recent years in worldwide comparison. In the future, the feedstock of biodiesel production can also be rape besides sunflower.According to the concept of harmonious development, the balance between nature, society, economy and human environments is represented by their mutual presumptive character. Research and development need to be aligned into this system. Our aim was to examine the advantages anddisadvantages of biodiesel production in different environments, using a model to do so. In order to maintain the harmony, the existing resources have to be managed properly, taking the correlations of the system into consideration. Targeted technological developments are necessary, similarly to the improvement of energy safety and efficiency.